Alfred Flechtheim. Raubkunst und Restitution - Bambi, Andrea; Drecoll, Axel (De Gruyter, 2015)
The tragic story of Alfred Flechtheim, his ideological defamation, and the loss of his art collection
English
German
Keywords: National Socialism; Restitution; Art Trade